ChemInform Abstract: The Defect Chemistry of Nitrogen in Oxides: A Review of Experimental and Theoretical Studies. Issue 14 (20th March 2013) - Polfus, Jonathan M.; Norby, Truls; Haugsrud, Reidar
Abstract Review: 106 refs.